Automation of Abnormal IP Blocking in Security Systems Using OCR-Driven Web Interaction and Real-Time Alert Integration - Yuzhen, Yin; Xiaoliang, Fang; Wei, Zhang (Journal of Cyber Security and Mobility, 2025)
The Shandong Earthquake Agency has established a comprehensive protection system that meets the national third-level safety requirements. However, challenges remain, such as delayed detection of malicious attacks and overly complex procedures for blocking abnormal IP addresses. To address these issues, this paper proposes a solution that leverages Selenium crawler technology, a Qt-based graphical user interface, and the integration of Baidu OCR and WeChat public account interfaces. The system enables simulated logins to network security equipment, real-time abnormal IP monitoring, automated alarm notifications, and automated interactions such as interface clicks and text input. With these functions, it achieves one-click blocking of abnormal IP addresses on security devices while storing related information for future reference. Since its deployment, the software has effectively enhanced the push of high-risk alarm information in the full-flow network security analysis system and streamlined the blocking of abnormal IPs in security devices such as firewalls, significantly improving the timeliness and efficiency of security protection.